Credit default swaps and shareholder monitoring - Yu, Xiaoxu (Nanyang Technological University, 2022)
The paper examines how the initiation of credit default swaps (CDSs) influence the firm’s shareholder monitoring intensity. Prior studies have provided evidence that CDSs decrease lenders’ monitoring over the referenced firm (Morrison, 2005; Parlour and Winton, 2013). However, there is scant literature on how shareholders react after the initiation of CDSs. Given that the reduced lenders’ monitoring could be detrimental to shareholders, I predict that shareholders will directly increase their monitoring intensity. Using a difference-in-differences design, I document that the shareholders’ monitoring intensity has significantly increased through director election voting and 13D filing after the initiation of CDSs. And the effect is concentrated on firms with higher firm risk, lower existing shareholders’ monitoring, and higher existing lenders’ monitoring. Collectively, the results provide direct evidence that shareholders indeed step in after firms’ CDSs initiation by enhancing their monitoring intensity.